Comparison of Total Phenolic Contents (TPC) and antioxidant activities of fresh fruit juices, commercial 100% fruit juices and fruit drinks - Khaw, Hui Wern; Hasnah Haron,; Chan, Boon Keng (Penerbit Universiti Kebangsaan Malaysia, 2016)
There is an increasing trend of fruit juice consumption due to increasing reported health benefits of antioxidant content present in fruit juices. The aim of this study was to compare the total phenolic contents (TPC) and antioxidant activities of fresh fruit juices, commercial 100% fruit juices and fruit drinks. Seven types of freshly blended fruit juices and their commercial counterparts were selected. Folin-Ciocalteu method was used to determine the total phenolic content, whilst ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays were performed to evaluate the antioxidant activities of fruit juices. The TPC contents of fresh fruit juices, commercial 100% fruit juices and fruit drinks were at the ranges of 13.38-80.40, 21.65-130.39 and 3.32-45.10 mg GAE/100 mL, respectively. Both fresh guava juice and commercial guava drinks have exhibited the highest antioxidant activities in DPPH assay (205.71-770.12 μmol TE/100 mL) and FRAP assay (320.80-843.13 μmol TE/100 mL). Pomegranate juices demonstrated the highest antioxidant activities among commercial 100% fruit juices with DPPH and FRAP values of 2705.01 and 2953.85 μmol TE/100 mL, respectively. Fruits drinks group had the lowest TPC and antioxidant activities for all types of fruits. TPC was significantly correlated (p<0.05) to FRAP (r=0.954) and DPPH (r=0.908) assays. In conclusion, the TPC and antioxidant activities of commercial 100% fruit juices and fresh juices were comparable as no significantly difference (p>0.05) was found between these two groups. Commercial fruit drinks in this study were not good source of antioxidants. These findings provide some useful information especially for ageing population in choosing healthy fruit juice or drinks for their health maintenance purposes.